2018
DOI: 10.1371/journal.pone.0203358
|View full text |Cite
|
Sign up to set email alerts
|

Virtual mortality and near-death experience after a prolonged exposure in a shared virtual reality may lead to positive life-attitude changes

Abstract: Mortality is an obvious if uncomfortable part of the human condition, yet it is impossible to study its impact on anyone who experiences it. Reports of phenomena associated with death such as out-of-the-body (OBE) and near death experiences (NDE) can only be studied post-hoc, since it is impossible to design a scientific study where an experimental group experiences death (and returns) and a control group does not. Yet NDEs seem to have a profound influence on the subsequent lives of people and are therefore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 72 publications
(86 reference statements)
2
27
0
2
Order By: Relevance
“…We assume that NDE-like memory, associated with positive emotions, may be induced in psychotherapy using hypnotic induction for therapeutic purposes. Moreover, a recent study showed that individuals who experienced embodiment using immersive virtual reality and witnessed a “simulated” NDE report positive life-attitude changes 56 . We thus believe that an integration of experimental and clinical research results might lead to the application of hypnosis in clinical and therapeutic contexts.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that NDE-like memory, associated with positive emotions, may be induced in psychotherapy using hypnotic induction for therapeutic purposes. Moreover, a recent study showed that individuals who experienced embodiment using immersive virtual reality and witnessed a “simulated” NDE report positive life-attitude changes 56 . We thus believe that an integration of experimental and clinical research results might lead to the application of hypnosis in clinical and therapeutic contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The Spanish translation of these questions and accompanying text used in the experiment, together with the original materials in English, are available at https://osf.io/f9ya7/. The Spanish version of the questions used in the experimental condition was taken verbatim from Barberia et al [21].…”
Section: Methodsmentioning
confidence: 99%
“…The Spanish translation of these questions and accompanying text used in the experiment, together with the original materials in English, are available at https://osf.io/f9ya7/. The Spanish version of the questions used in the experimental condition was taken verbatim from Barberia, Oliva, Bourdin, and Slater (2018).…”
Section: Methodsmentioning
confidence: 99%